Associations between risk behavior and injury and the protective roles of social environments: an analysis of 7235 Canadian school children. Issue 2 (3rd April 2006) - Pickett, W; Dostaler, S; Craig, W; Janssen, I; Simpson, K; Shelley, S Danielle; Boyce, W F
Abstract : Objective: The social etiology of adolescent injury remains poorly understood. The Population Health Framework suggests that the etiology of adolescent injury involves interactions between individual risk factors and the natures of adolescent environments. The purpose of this study was to apply this framework to examination of relationships between adolescent risk taking and injury, and the potential modifying effects of supportive home and school environments. Methods: The analysis was conducted in a representative sample of 7235 males and females (10–16 years old) from Canada. Results were based on records from the 2001/02 World Health Organization Health Behaviour in School-Aged Children Survey . Individual items and factor analytically derived scales were used to describe and then model injury outcomes, risk behaviors, perceived home, and school climates, and the relationships between these variables in a theory driven etiological analysis. Results: Adolescents with supportive home and school environments experienced lower relative odds of engagement in risk taking behavior and lower relative odds of injury. Gradients were observed between the extent of adolescent risk taking and the occurrence of injury. Interactions were not observed between risk taking behavior, perceived support in home and school climates, and injury. Conclusions: Risk taking is common among adolescents and plays a role in the etiology of injury. Supportive social climates clearly protect adolescents from engaging in these behaviors, and also the occurrence of some forms of injury. However, once an adolescent chooses to engage in risk taking behaviour, a supportive environment may not protect them from injury.